Sosialisasi dan Pelatihan Perawatan Mesin Perahu untuk Menigkatkan Keterampilan Nelayan Dipesisir Pantai Ketaping Kabupaten Padang Pariaman - Uddin, Soleh; Syamsyir, Syamsyir; Erlinda, Nelfi; Basrizal, Basrizal; Kyozi, Kyozi; Luban T, Putra Cristofer Noventius (Abdimas Indonesian Journal, 2025)
This community service activity was carried out to improve the knowledge and skills of fishermen in Ketaping Beach, Padang Pariaman Regency, in maintaining and repairing boat engines. The background of this activity is the low awareness of fishermen of safety at sea and the frequent breakdown of boat engines during operation. The methods used are in the form of socialization and training consisting of lectures, discussions, and the practice of disassembling boat engine components. The results of the activity showed that there was an increase in fishermen's understanding of work safety and boat engine maintenance techniques. The fishermen also gave a very positive response and hoped that similar activities could continue in the future. This activity is expected to be able to reduce the risk of engine damage at sea, increase the efficiency of seagoing activities, and encourage the improvement of the welfare of fishermen in Ketaping.